2017
DOI: 10.18203/2394-6040.ijcmph20173169
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication practices versus health of the community

Abstract: Background: Self-medication is a common practice worldwide and the irrational use of drugs is a cause of concern. Self-medication involves the use of medicinal products by the individuals to treat self-recognized disorders or symptoms, or the intermittent or continuous use of a medication prescribed by a physician for chronic or recurring diseases or symptoms. The objectives of the study were to find out the prevalence of self-medication practices in the community; to describe the common conditions where self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
3
6
1
Order By: Relevance
“…However, the consumption of drugs prescribed by medical practitioners was higher, as well as the presence of chronic diseases. These results, although at a lower percentage (23%), were similar to those obtained by Dutta et al in a rural population [ 20 ]. This may be due to different factors such as: the availability of these drugs in pharmacies, the consumption of advertising through the media and social networks [ 21 ], the greater presence of acute illness, lifestyle, and living in an urban population.…”
Section: Discussionsupporting
confidence: 91%
“…However, the consumption of drugs prescribed by medical practitioners was higher, as well as the presence of chronic diseases. These results, although at a lower percentage (23%), were similar to those obtained by Dutta et al in a rural population [ 20 ]. This may be due to different factors such as: the availability of these drugs in pharmacies, the consumption of advertising through the media and social networks [ 21 ], the greater presence of acute illness, lifestyle, and living in an urban population.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the extent of self-medication was found to be 73.6%, relatively similar to studies in Pakistan (64%), 43 Bangladesh (71.4%), 44 and Ethiopia (71.4%) 8 that were conducted in the analogous context of the COVID-19 pandemic, though greater than findings in Brazil (14.9%), 45 Tamil Nadu (17.8%), 46 Saudi Arabia (35.4%), 47 and India (35.1%). 14 Other results from Ethiopia in different towns further strengthen this difference: Welaita Soddo (33.7%), 48 Jijiga (37.5%), 2 Dessie (42.4%), 49 and Gonder (50.2%).…”
Section: Discussionsupporting
confidence: 85%
“…This study was conducted among 200 participants in urban and 200 in rural area. This study revealed that in urban and rural area most of the participants are males [15][16][17] In the present study most of the participants in urban area belonged to nuclear family (51.0%) and rest are belonged to joint (26.5%) and three generation family (22.5%) while in rural area half of the participants belonged to joint family and those belonging to nuclear family were (40.0%) and three generation family (10%) respectively. On the other hand study conducted by Dutta et al in Chennai, Tamil Nadu reported that 62.5% participants were belong to nuclear family and rest are belong to third generation and joint family.…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand study conducted by Dutta et al in Chennai, Tamil Nadu reported that 62.5% participants were belong to nuclear family and rest are belong to third generation and joint family. 15 In urban and rural areas most of the people were educated upto middle grade of education (22.0%, 27.5%) followed by illiterate ( 18,19 The difference in educational status is because of difference in literacy rate in different place of previous study The difference observed is mainly because of difference in socio-economic status condition in the various study areas.…”
Section: Discussionmentioning
confidence: 96%